Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Improved estimation of aquaculture associated European introgression in a captive breeding program for endangered Atlantic salmon - Melissa K. Holborn; Tony Kess; Cameron M. Nugent; Nathalie N. Brodeur; Joke Adesola; Evan Cronmiller; Lorraine C. Hamilton; Ross A. Jones; Beth L. Lenentine; Anna MacDonnell; Meghan McBride; Amber Messmer; et al. (Conservation Genetics, 2025)
The rapid, range-wide decline in Atlantic salmon, Salmo salar , populations is well documented and has led to establishment of captive rearing and breeding programs in order to preserve populations. However, recovery potential may be limited by the inclusion of non-local genotypes, which can be both difficult to detect and quantify. In the genetically unique Inner Bay of Fundy population located in Canada, three Live Gene Bank programs have been established to aid recovery of this endangered conservation unit. Evidence of aquaculture associated non-local (i.e., European) introgression had previously been detected using small panels of microsatellite markers with limited power. Here we show how advances in sequencing and machine learning technologies can support a conservation program. We used machine learning and a corresponding panel of 301 SNPs to estimate individual-level proportions of European ancestry. To assess the degree of introgression in each program and to assess changes over time, fish were randomly selected across several program generations. Estimates were validated by genotyping a subset of individuals on a 220 K SNP array and using established admixture methods. Of the 1741 fish analyzed, only 48 were found to have European ancestry greater than the detection threshold. We found the amount of European ancestry was previously overestimated, and that very few wild-collected founder individuals had large proportions of European ancestry. Moreover, because European ancestry was introduced to Bay of Fundy populations via introgression from aquaculture escapees, these values represent the minimum amount of aquaculture introgression in these captive populations.

Testing a rapid assessment approach for estimating ecosystem service capacity in urban green alleys - Marie C. Dade; Isabella C. Richmond; Jesse T. Rieb; Erin T.H. Crockett; Kayleigh Hutt-Taylor; Serena Sinno; Karina Benessaiah; Catherine Destrempes; Jacqueline Hamilton; Fatemeh Izadi; L. Emily Kroft; Lingshan Li; et al. (Urban Forestry & Urban Greening, 2024)

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Evaluating a microalga (Schizochytrium sp.) as an alternative to fish oil in fish-free feeds for sablefish (Anoplopoma fimbria) - Katherine A. Neylan; Ronald B. Johnson; Frederic T. Barrows; David P. Marancik; Scott L. Hamilton; Luke D. Gardner (Aquaculture, 2024)

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Scavenging dynamics on Guam and implications for invasive species management - Jacob E. Hill; Kelsey L. Turner; Joshua B. Smith; Matthew T. Hamilton; Travis L. DeVault; William C. Pitt; James C. Beasley; Olin E. Rhodes (Biological Invasions, 2023)

Conventional loose mineral with added red clover leaf (Trifolium pratense L.) reverses vasoconstriction associated with tall fescue toxicosis in steers - Brittany E. Davis; Tracy A. Hamilton; John T. Johns; David L. Harmon; James L. Klotz; Jennifer R. Weinert-Nelson; Jack P. Goodman; John May; Huihua Ji; F. Neal Schrick; Michael D. Flythe (Animal Feed Science and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Coupled changes in pH, temperature, and dissolved oxygen impact the physiology and ecology of herbivorous kelp forest grazers - Emily M. Donham; Lauren T. Strope; Scott L. Hamilton; Kristy J. Kroeker (Global Change Biology, 2022)
Understanding species’ responses to upwelling may be especially important in light of ongoing environmental change. Upwelling frequency and intensity are expected to increase in the future, while ocean acidification and deoxygenation are expected to decrease the pH and dissolved oxygen (DO) of upwelled waters. However, the acute effects of a single upwelling event and the integrated effects of multiple upwelling events on marine organisms are poorly understood. Here, we use in situ measurements of pH, temperature, and DO to characterize the covariance of environmental conditions within upwelling‐dominated kelp forest ecosystems. We then test the effects of acute (0–3 days) and chronic (1–3 months) upwelling on the performance of two species of kelp forest grazers, the echinoderm, Mesocentrotus franciscanus , and the gastropod, Promartynia pulligo . We exposed organisms to static conditions in a regression design to determine the shape of the relationship between upwelling and performance and provide insights into the potential effects in a variable environment. We found that respiration, grazing, growth, and net calcification decline linearly with increasing upwelling intensity for M . francicanus over both acute and chronic timescales. Promartynia pulligo exhibited decreased respiration, grazing, and net calcification with increased upwelling intensity after chronic exposure, but we did not detect an effect over acute timescales or on growth after chronic exposure. Given the highly correlated nature of pH, temperature, and DO in the California Current, our results suggest the relationship between upwelling intensity and growth in the 3‐month trial could potentially be used to estimate growth integrated over long‐term dynamic oceanographic conditions for M . franciscanus . Together, these results indicate current exposure to upwelling may reduce species performance and predicted future increases in upwelling frequency and intensity could affect ecosystem function by modifying the ecological roles of key species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Biofilm Formation by Avian Pathogenic Escherichia coli is Not Related to In Vivo Pathogenicity - Suelle V. Rodrigues; Vanessa Laviniki; Karen A. Borges; Thales Q. Furian; Hamilton L. S. Moraes; Vladimir P. Nascimento; Carlos T. P. Salle (Current Microbiology, 2019)

Heparin impairs angiogenic signaling and compensatory lung growth after left pneumonectomy - Duy T. Dao; Lorenzo Anez-Bustillos; Jared Ourieff; Amy Pan; Paul D. Mitchell; Hiroko Kishikawa; Gillian L. Fell; Meredith A. Baker; Randolph S. Watnick; Hong Chen; Thomas E. Hamilton; Michael S. Rogers; et al. (Angiogenesis, 2018)

Diel behavior in moths and butterflies: a synthesis of data illuminates the evolution of temporal activity - Akito Y. Kawahara; David Plotkin; Chris A. Hamilton; Harlan Gough; Ryan St Laurent; Hannah L. Owens; Nicholas T. Homziak; Jesse R. Barber (Organisms Diversity & Evolution, 2018)

Effects of selenium exposure on the hematology, innate immunity, and metabolic rate of yellow-bellied sliders (Trachemys scripta scripta) - David L. Haskins; Matthew T. Hamilton; Nicole I. Stacy; John W. Finger; Tracey D. Tuberville (Ecotoxicology, 2017)

Variability in the chemistry of private drinking water supplies and the impact of domestic treatment systems on water quality - E. L. Ander; M. J. Watts; P. L. Smedley; E. M. Hamilton; R. Close; H. Crabbe; T. Fletcher; A. Rimell; M. Studden; G. Leonardi (Environmental Geochemistry and Health, 2016)

Reduction of Ethanol Yield from Switchgrass Infected with Rust Caused by Puccinia emaculata - Virginia R. Sykes; Fred L. Allen; Jonathan R. Mielenz; C. Neal Stewart; Mark T. Windham; Choo Y. Hamilton; Miguel Rodriguez; Kelsey L. Yee (BioEnergy Research, 2016)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Developing Marine Protected Area Networks in the Coral Triangle: Good Practices for Expanding the Coral Triangle Marine Protected Area System - Rebecca Weeks; Porfirio M. Aliño; Scott Atkinson; Pacifico Beldia; Augustine Binson; Wilfredo L. Campos; Rili Djohani; Alison L. Green; Richard Hamilton; Vera Horigue; Robecca Jumin; Kay Kalim; et al. (Coastal Management, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Quantifying the production of dissolved organic nitrogen in headwater streams using 15 N tracer additions - Laura T. Johnson; Jennifer L. Tank; Robert O. Hall, Jr.; Patrick J. Mulholland; Stephen K. Hamilton; H. Maurice Valett; Jackson R. Webster; Melody J. Bernot; William H. McDowell; Bruce J. Peterson; Suzanne M. Thomas (Limnology and Oceanography, 2013)
Most nitrogen (N) assimilation in lake and marine ecosystems is often subsequently released via autochthonous dissolved organic nitrogen (DON) production, but autochthonous DON production has yet to be quantified in flowing waters. We measured in‐stream DON production following 24 h 15 N‐nitrate () tracer additions in 36 headwater streams, a subset of sites from the second Lotic Intersite Nitrogen eXperiment. Streams were located in five North American ecoregions and drained basins dominated by native vegetation, agriculture, or urban land use. Using a two‐compartment model, we could quantify DON production in 15 streams as a function of DO 15 N derived from 15 N tracer in biomass compartments. The streams with detectable DON production had higher % modified land use (agriculture + urban) in their basins than did streams with undetectable DON production. Median DON production represented 8% of total uptake when we used N biomass estimates based on N assimilated over 1 d (measured directly from the 15 N additions). Median DON production was 17% of total uptake when we used N assimilated over 42 d (extrapolated from previous 15 N tracer studies). Variation in DON production was positively correlated with ecosystem respiration, indicating that stream heterotrophy may influence DON production. In‐stream DON production was similar in magnitude to stream denitrification and nitrification, indicating that the production of autochthonous DON can represent a substantial transformation of stream N. Our results confirm that headwater streams can quickly convert inorganic N into organic forms, although the ultimate fate of DON remains unclear.

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

Research partnerships with local communities: two case studies from Papua New Guinea and Australia - G. R. Almany; R. J. Hamilton; D. H. Williamson; R. D. Evans; G. P. Jones; M. Matawai; T. Potuku; K. L. Rhodes; G. R. Russ; B. Sawynok (Coral Reefs, 2010)

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

Conserved regulatory motifs at phenylethanolamine N-methyltransferase (PNMT) are disrupted by common functional genetic variation: an integrated computational/experimental approach - Juan L. Rodríguez-Flores; Kuixing Zhang; Sun Woo Kang; Gen Wen; Sajalendu Ghosh; Ryan S. Friese; Sushil K. Mahata; Shankar Subramaniam; Bruce A. Hamilton; Daniel T. O’Connor (Mammalian Genome, 2010)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Assimilatory uptake rather than nitrification and denitrification determines nitrogen removal patterns in streams of varying land use - C. P. Arango; J. L. Tank; L. T. Johnson; S. K. Hamilton (Limnology and Oceanography, 2008)
Agricultural and urban land use increase nitrogen (N) concentrations in streams, which can saturate biotic demand by plants, algae, and bacteria via assimilative uptake, and by nitrification and denitrification. We studied six streams per year in each of three land‐use categories (agricultural, urban, and forested) for 3 yr ( n = 18 streams), and we compared whole‐stream N uptake and microbial N transformation rates during spring, summer, and autumn. We measured whole‐stream removal of added ammonium (NH 4 + ) and nitrate (NO 3 − ) in the field and quantified sediment nitrification and denitrification rates in laboratory assays. Relative demand for NNH 4 + (as uptake velocity, Vf) was highest in spring and in streams with open canopies, implying a link with aquatic autotrophy. In agricultural and urban streams, whole‐stream removal (as areal uptake, U) of NH 4 + and NO 3 − , nitrification, and denitrification rates approached saturation at higher inorganic N concentrations. Nitrification and denitrification rates measured in redox‐optimized laboratory assays were roughly equivalent, suggesting that in situ redox conditions will determine whether stream sediments are a net source or sink of NO 3 − . Though nitrification and denitrification rates were measured under ideal redox conditions, they were always more than an order of magnitude lower than whole‐stream NO{3 uptake, demonstrating their limited influence on wholestream NO 3 − dynamics. Assimilatory processes, which temporarily store N removed from the water column, dominated whole‐stream N demand and controlled downstream N flux. The ultimate fate of assimilated N remains unknown; in‐channel storage cannot account for it, and thus a key question is what fraction may eventually be stored in downstream depositional zones or denitrified upon remineralization.

Regional-scale models for relating land cover to basin surface-water quality using remotely sensed data in a GIS - V. L. Versace; D. Ierodiaconou; F. Stagnitti; A. J. Hamilton; M. T. Walter; B. Mitchell; A.-M. Boland (Environmental Monitoring and Assessment, 2008)

Patterns of male reproductive success in a highly promiscuous whale species: the endangered North Atlantic right whale - T. R. FRASIER; P. K. HAMILTON; M. W. BROWN; L. A. CONGER; A. R. KNOWLTON; M. K. MARX; C. K. SLAY; S. D. KRAUS; B. N. WHITE (Molecular Ecology, 2007)
Parentage analyses of baleen whales are rare, and although mating systems have been hypothesized for some species, little data on realized male reproductive success are available and the patterns of male reproductive success have remained elusive for most species. Here we combine over 20 years of photo‐identification data with high‐resolution genetic data for the majority of individual North Atlantic right whales to assess paternity in this endangered species. There was significant skew in male reproductive success compared to what would be expected if mating was random ( P 0.001). The difference was due to an excess of males assigned zero paternities, a deficiency of males assigned one paternity, and an excess of males assigned as fathers for multiple calves. The variance in male reproductive success was high relative to other aquatically mating marine mammals, but was low relative to mammals where the mating system is based on resource‐ and/or mate‐defence polygyny. These results are consistent with previous data suggesting that the right whale mating system represents one of the most intense examples of sperm competition in mammals, but that sperm competition on its own does not allow for the same degree of polygyny as systems where males can control access to resources and/or mates. The age distribution of assigned fathers was significantly biased towards older males ( P 0.05), with males not obtaining their first paternity until ~15 years of age, which is almost twice the average age of first fertilization in females (8 years), suggesting that mate competition is preventing younger males from reproducing. The uneven distribution of paternities results in a lower effective population size in this species that already has one of the lowest reported levels of genetic diversity, which may further inhibit reproductive success through mate incompatibility of genetically similar individuals.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

World‐wide genetic differentiation of Eubalaena : questioning the number of right whale species - H. C. Rosenbaum; R. L. Brownell; M. W. Brown; C. Schaeff; V. Portway; B. N. White; S. Malik; L. A. Pastene; N. J. Patenaude; C. S. Baker; M. Goto; P. B. Best; et al. (Molecular Ecology, 2000)
Few studies have examined systematic relationships of right whales ( Eubalaena spp.) since the original species descriptions, even though they are one of the most endangered large whales. Little morphological evidence exists to support the current species designations for Eubalaena glacialis in the northern hemisphere and E. australis in the southern hemisphere. Differences in migratory behaviour or antitropical distribution between right whales in each hemisphere are considered a barrier to gene flow and maintain the current species distinctions and geographical populations. However, these distinctions between populations have remained controversial and no study has included an analysis of all right whales from the three major ocean basins. To address issues of genetic differentiation and relationships among right whales, we have compiled a database of mitochondrial DNA control region sequences from right whales representing populations in all three ocean basins that consist of: western North Atlantic E. glacialis , multiple geographically distributed populations of E. australis and the first molecular analysis of historical and recent samples of E. glacialis from the western and eastern North Pacific Ocean. Diagnostic characters, as well as phylogenetic and phylogeographic analyses, support the possibility that three distinct maternal lineages exist in right whales, with North Pacific E. glacialis being more closely related to E. australis than to North Atlantic E. glacialis . Our genetic results provide unequivocal character support for the two usually recognized species and a third distinct genetic lineage in the North Pacific under the Phylogenetic Species Concept, as well as levels of genetic diversity among right whales world‐wide.

Microsatellite loci reveal highly significant genetic differentiation among Atlantic salmon ( Salmo salar L.) stocks from the east coast of Canada - S. K. J. McConnell; D. E. Ruzzante; P. T. O'Reilly; L. Hamilton; J. M. Wright (Molecular Ecology, 1997)
Allele frequency data from eight microsatellite loci provide evidence of highly significant genetic differentiation among stocks of Atlantic salmon Salmo salar L. from the Bay of Fundy, eastern and north‐western Nova Scotia and Newfoundland. Estimates of genetic structure ( R ST and θ) were significant both among all samples taken from the different geographical locations and among samples from geographical regions for which more than one stock was sampled. Samples from the Bay of Fundy taken from stocks which are phenotypically and behaviourally diverse showed particularly high levels of genetic structure. Rogers', allele sharing and (δμ) 2 distances also revealed significant differences among stock samples and were significantly correlated [Rogers' and (δμ) 2 ] with sea distance between rivers. Results suggest that stocks of Atlantic salmon in eastern Canada are highly diverse genetically and that this should be an important consideration in any management programme for stocks in the area.

Impedance-measuring ventilation monitor for infants - L. H. Hamilton; W. T. Bruns (Annals of Biomedical Engineering, 1973)